Telehealth application on the rehabilitation of children and adolescents - Maria Tereza N. dos Santos; Sarah Costa D. O. Moura; Ludmila Mourao X. Gomes; Ana Henriques Lima; Rafaela Silva Moreira; Caroline Duarte Silva; Eliane Marina P. Guimaraes (Sociedade de Pediatria de São Paulo, 2014)
Objective: To systematically review the literature on the telehealth initiatives in telerehabilitation practices in children and adolescents from zero to 18 years old. Data sources: Randomized and controlled clinical trials published in the past ten years (January 2002 to February 2012) in Medline/PubMed, Medline/BVS, PEDro and Cochrane Library databases. The descriptors "telemedicine", "rehabilitation" and "telehealth" were used in three different languages (English, Portuguese and Spanish). Data synthesis: From the 20 studies found in the literature, nine were included in this review. Most of the studies showed that telerehabilitation is able to produce better results in the treatment when compared to the traditional methods, providing less frequency of symptoms, better disease control, better quality of life and greater adherence to treatment. Conclusions: Telerehabilitation is a viable and effective strategy in the treatment of common diseases in children and adolescents. However, there are few studies on the subject in this age group. Although telehealth is already consolidated worldwide, there are no studies in Brazil that used the telerehabilitation in children and adolescents, which reinforces the need for more research and investments.